2017
DOI: 10.33830/jom.v13i2.66.2017
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Partisipasi Anggaran, Asimetri Informasi, Tekanan Anggaran Dan Komitmen Organisasi Terhadap Senjangan Anggaran Di Pemerintah Kabupaten Banyumas

Abstract: This study aims to determine the effect of budgetary participation, information asymmetry, budget pressure, and organizational commitment to budgetary slack. Population in this research is all government institution in Banyumas Regency. The sample selection was conducted by census method. Dependent variable used in this research is budget slack, while the independent variable used in this research is budget participation, information asymmetry, budget pressure, and organizational commitment. The data has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Berlakunya otonomi dan desentralisasi daerah di Indonesia mengakibatkan akuntabilitas atau pertanggungjawaban vertikal pada pemerintah pusat berubah menjadi pertanggungjawaban horizontal kepada masyarakat (Permana, Herwiyanti, & Mustika, 2017). Pada organisasi sektor publik saat anggaran menjalankan program dengan menggunakan dana yang juga milik masyarakat (Putri et al, 2016).…”
Section: Pendahuluanunclassified
“…Berlakunya otonomi dan desentralisasi daerah di Indonesia mengakibatkan akuntabilitas atau pertanggungjawaban vertikal pada pemerintah pusat berubah menjadi pertanggungjawaban horizontal kepada masyarakat (Permana, Herwiyanti, & Mustika, 2017). Pada organisasi sektor publik saat anggaran menjalankan program dengan menggunakan dana yang juga milik masyarakat (Putri et al, 2016).…”
Section: Pendahuluanunclassified
“…Dengan demikian, partisipasi penyusunan anggaran pada penelitian ini memiliki pengaruh negatif terhadap senjangan anggaran. Ini sejalan dengan hasil penelitian yang dilakukan oleh (Kusniawati & Lahaya, 2017), (Afdhal et al, 2021), (Permana et al, 2017), dan (Yandriyan, 2019) yang menyatakan partisipasi penyusunan anggaran tidak berpengaruh terhadap senjangan anggaran.…”
Section: Uji Inner Model R-square (R 2 )unclassified
“…Research conducted by Putri et al (2017), and Kalembang et al (2018) said that budgetary participation has a positive effect on budgetary slack where the higher the budgetary participation, the higher the budgetary slack. However, different research results obtained by Permana et al (2017) and Yandriyan (2019) showed a negative influence between budgetary participation and budgetary slack namely saying that participation can affect the decrease in budgetary slack, which is characterized by positive communication between managers so that subordinates are not compelled to create budgetary slack.…”
Section: Introductionmentioning
confidence: 95%
“…This theory states that when a business deals with an incomplete information and uncertainty condition, agency problems will arise in the form of moral hazard and unfavorable choices. Moral hazard is a condition where the principal is not sure that the agent uses his ability to work appropriately without thinking about the rewards he receives (Kahar and Chariri, 2016 (Permana et al, 2017). If there is a budgetary slack, then the performance will increase because it can reach the revenue target or able to reduce costs below the budget figure.…”
Section: Literature Reviewmentioning
confidence: 99%